Coastal wetlands of indonesia : - Furukawa, Hisao (Kyoto University Press, 1994)
Coastal wetlands the frontiers of the melayu world. An overview of the natural history of the wetlands. natural environmental of the coastal wetlands. Land use and traditional occupations. Large-scale reclamation of the tidal zones. The melayu world, a culture of trasit.